Producing beef meat under hard livestock conditions by crossing cattle with Belgian Blue-White breed. Preliminary study - Allouche L.; Madani T.; Mechmeche M.; Bouchemal A. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
Crossing cows with pure meat breed bull as Charolais and Belgian Blue-White is widely used in the world for beef meat production. In Algeria, more than 100 cows from different breeds as Montbeliarde, Fleckvieh and Holstein were inseminated by a single Belgian Blue-White bull in Sétif (Algeria), a semi-arid region where the temperature can reach 45°C in Summer and -4°C in winter. Calves were weighed at birth and at the age of one year. Our preliminary results show that the frequency of pregnancy was very high after the first insemination (78%). Also, the total pregnancy rate was very satisfactory (95%). Most of calves were born easily or with few assistances from the breeders (92%). Cross calves born in Algeria and bred under hard conditions reached around 500 Kg of weight at one year old whose the heaviest calf weighed 570 Kg. However, the cross calves born from the Montbeliarde cows were heavier by 59 Kg than those born from Fleckvieh cows. Such kind of projects can contribute to food security, create employment in rural areas and consequently limit the immigration.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)